Property cases, documents, and lawyering strategies - Crump, David 1943-; Caudill, David Stanley 1952-; Hricik, David (Carolina Academic Press, 2020)
"This Property casebook makes the topic of Property Law come to life by emphasizing aspects of property transactions that are important today. At the same time, its organization and coverage reflects customary course coverage. On the one hand, the broad subjects covered in this book are traditional. Personal property, real estate transactions, servitudes, leases, common law estates, and land regulation-the subjects that long have formed the backbone of the Property course - are all present. On the other hand, this is a course for the Twenty-First Century. Personal property is treated through coverage of intellectual property: patents, copyrights, trademarks, and trade secrets. Property transactions are approached from the point of view of a contemporary lawyer representing a client. The book covers current documents, contemporary doctrines, and relevant concepts"--
Index
Keywords: Real property / United States / Cases; Property / United States / Cases; Property; Real property; United States; Casebooks (Law); Trials, litigation, etc